"Stony ground but not entirely": On the metaphor of "grace" in Alain Badiou. (2nd January 2018) - Karlsen, Mads Peter
Abstract : Even though Alain Badiou depicts himself and his philosophy as "militant atheist" there is, as he himself has pointed out, nevertheless several theological notions present in his work. This presence of theological language is not restricted to his book on the Apostle Paul, but can be found throughout his work. This paper focuses on Badiou's substantial use of the term "grace" as a metaphor for the exceptional occurrence that he defines in philosophical terms as an "event". The aim of the paper is to identify the context in which Badiou comes to use, and the sources from which he draws the metaphor of "grace", and thus to contribute to a more precise understanding of what he means by this metaphor. The paper will identify the key instances in which Badiou employs the term "grace" in an effort to clarify how he understands it and what ends he intends it to serve. And in contrast to the existing research concerning the issue of grace, in which there has been a tendency to centre the attention almost entirely on Badiou's book on Paul, it will consider a number of different instances in which he uses this term.